Prevalence of Eimeria spp. infections and major histocompatibility complex class II DRA diversity in Mongolian Bactrian camels (Camelus bactrianus) - Khatanbaatar, Igori; Nyamdolgor, Uranbileg; Chinchuluun, Boldbaatar; Naranbaatar, Khandsuren; Taubert, Anja; Hermosilla, Carlos R.; Suchentrunk, Franz; Knauer, Felix; Burger, Pamela A.; Battsetseg, Gonchigoo (Frontiers in Veterinary Science, 2023)
The two-humped Bactrian camel (Camelus bactrianus) is a large, even-toed ungulate native to the steppes of Central Asia. Domestic Bactrian camels are economically important in Mongolia and other Central Asian countries. These animals are used for transport, milk and meat production, and camel racing which is a great culture of nomads. Eimeriosis, also known as coccidiosis, is considered as an economically important parasitic diseases in Bactrian camels. There is still considerable lack of data concerning the spectrum of monoxenous Eimeria species, their epizootiology as well as their precise life cycles in Bactrian camels. This study was performed to determine the prevalence of Eimeria species in camelids from southern part of Mongolia. A total of 536 fresh camel fecal samples (n = 536) collected from herds located in five different Aimags (provinces) of Mongolia were examined. Eimeria spp. oocysts were isolated using the sugar flotation technique, and after sporulation, oocysts were identified by morphometric evaluation. We identified the most common Eimeria species infecting Mongolian Bactrian camels: Eimeria cameli (22.3 %), Eimeria rajasthani (37.3 %) and Eimeria dromedarii (27.7 %). Interestingly, mixed infections were detected in 24.8 % (n = 133) of the samples, while 39.0 % (n = 209) were negative for coccidian stages. To investigate the immunogenetic response of the Mongolian Bactrian camels to Eimeria spp. infection, we screened the genetic diversity in a functional important immune response gene of the major histocompatibility complex (MHC). We detected two polymorphic sites in the MHC class II DRA exon 2, which translated into one non-synonymous and one synonymous amino acid (aa) change. The resulting aa alleles were not significantly associated with any of the three detected Eimeria species infections, nor could we show heterozygote advantage in non-infected Mongolian Bactrian camels. Further investigations on molecular epidemiology, in vitro culture, pathogenicity and host-parasite interactions will be necessary to better understand the impact of eimeriosis in Bactrian camels.